Upaya Komunikasi Angel Perias Wajah Dalam Promosi Melalui Media Sosial - Revolver, Angeline; Edlina, Ria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This final report was written to find out the communication efforts of makeup artists in Instagram social media promotions. In business, communication usually requires effective communication, one of which is promotion to face competition in selling products/services in order to create success in achieving business goals. Angel Makeup is a business operating in the field of make-up services which is domiciled in the city of Padang. Angel makeup artist provides women's makeup services, with various types of makeup looks to suit consumer needs. Therefore, in writing this final assignment, the researcher describes how Angel makes up her efforts in using Instagram social media as a means of promotion for the community, especially in the city of Padang. Makeup is one way to beautify yourself. Makeup is a market that has a high level of competition, this can be seen from the many types of makeup products that are produced domestically and imported from abroad. The high public interest in makeup has become a reference for other people to become a business field, and not just a product business, but makeup can also be a service business, one of which is a makeup artist. In 2016, a survey proved that there were 6000 MUA (Makeup Artists), and in 2021 there were more than 10,000 beauty service providers including makeup services in 35 cities in Indonesia.